If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 19 + -42 = 3(x + -2) + -8 Combine like terms: 19 + -42 = -23 -23 = 3(x + -2) + -8 Reorder the terms: -23 = 3(-2 + x) + -8 -23 = (-2 * 3 + x * 3) + -8 -23 = (-6 + 3x) + -8 Reorder the terms: -23 = -6 + -8 + 3x Combine like terms: -6 + -8 = -14 -23 = -14 + 3x Solving -23 = -14 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -23 + -3x = -14 + 3x + -3x Combine like terms: 3x + -3x = 0 -23 + -3x = -14 + 0 -23 + -3x = -14 Add '23' to each side of the equation. -23 + 23 + -3x = -14 + 23 Combine like terms: -23 + 23 = 0 0 + -3x = -14 + 23 -3x = -14 + 23 Combine like terms: -14 + 23 = 9 -3x = 9 Divide each side by '-3'. x = -3 Simplifying x = -3
| -2+9=14x-3-13x | | -5c+2=-18 | | -5(x+1)-11=21+3 | | 12(x-3)=-3-9 | | -2+5x=-32 | | 3x^3-9x^2+8x-7=2 | | 3(5y-4)=9y | | 6-x=20 | | -117=2(1-6p)-5p | | 5(5c-1)-4=21c+3 | | -(-9x-9y+4)= | | 3.5x=21 | | 4y^2-25x^2=100 | | 144=16t^2 | | 5=p+3 | | .3x+1.8=8 | | 3a-8a= | | 15x-2y=10 | | 5-.5x-3=4 | | 43y=6(7y-2) | | 6y=5(y+3) | | (x-3)(2x+3)=0 | | 5x^2=75 | | -2x-3-x=-3(-2x+7) | | 5x^2+25=100 | | 3(2x-3)=7 | | x^2+36=11 | | 2x^2+25=25 | | 2x^2-25=25 | | 2z^2+5=167 | | 15x+3y=12 | | 2x+5x+34*6/46=8 |